ANALISIS AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN ALOKASI DANA DESA DALAM PEMBANGUNAN DI DESA (Studi Kasus di Desa Lewobunga Kecamatan Adonara Timur Kabupaten Flores Timur) - Nuraini Ismail; Apriana Marselina; Elisabeth Yelita Weni (Jurnal Mirai Management, 2023)
Village Financial Management is a whole activity that includes planning, implementing, administering, reporting and accountability of village finances. This research aims to analyze the Accountability and Transparency of managing village fund allocations in Lewobunga Village, East Adonara District, East Flores Regency. The research method used is descriptive qualitative using data collection techniques of observation, interviews, documentation and literature study. The results of the study showed that Accountability and Transparency in Lewobunga Village were largely not in accordance with Permendagri No. 20 of 2018. The planning stage lacked cooperation between the village government and village communities and the results of discussing plans to use Village Fund Allocations were not informed to the public. The implementation stage of the government's performance has not been carried out properly because the community did not receive information regarding the allocation of village funds. The reporting stage is late in submitting the final report on the realization of the implementation of activities and the budget. The accountability stage lacks clarity, openness and convenience for the public to be able to access information about budget details. Keywords: Accountability, Transparency, Allocation of Village Funds (ADD)